Case Based Reasoning Untuk Diagnosa Kecanduan Terhadap Game Berbasis Web - Jhordi, Rafif; Dwidasmara, Ida Bagus Gede; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p81, 2022)
Online games in Indonesia have been loved by small children to adults in Indonesia. The Organization (WHO) defines game addiction or game disorder in the latest version of the International Statistical Classification of Diseases (ICD) as a mental disorder condition. Case Based Reasoning (CBR) has been a successful technique for knowledge-based systems in many domains. Case-based Reasoning (CBR) collects previous cases that are almost the same as the new problem and tries to modify the solution to fit the new case. The implementation of this expert system is so that online game users can find out early whether online game users have entered the addict category or not, so addicts are expected to reduce the use of online games.